2011
DOI: 10.1038/npp.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Blockade of 5-HT7 Receptors as a Putative Fast Acting Antidepressant Strategy

Abstract: Current antidepressants still display unsatisfactory efficacy and a delayed onset of therapeutic action. Here we show that the pharmacological blockade of serotonin 7 (5-HT 7 ) receptors produced a faster antidepressant-like response than the commonly prescribed antidepressant fluoxetine. In the rat, the selective 5-HT 7 receptor antagonist SB-269970 counteracted the anxiogenic-like effect of fluoxetine in the open field and exerted an antidepressant-like effect in the forced swim test. In vivo, 5-HT 7 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 96 publications
4
98
0
2
Order By: Relevance
“…It has been shown that the blockade of 5-HT 7 receptors increases 5-HT raphe-hippocampus transmission [11]. Enhancement of 5-HT transmission in such projection areas as the dorsal hippocampus after 1 week of SB 269970 administration has also been reported by other researchers [42]. On the other hand, some authors have found that the 5-HT 7 receptor antagonist SB 269970 significantly inhibits 5-HT efflux [51]; however, other investigators have shown that inhibition of 5-HT release is likely to be mediated by 5-HT 7 receptor agonists [22].…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…It has been shown that the blockade of 5-HT 7 receptors increases 5-HT raphe-hippocampus transmission [11]. Enhancement of 5-HT transmission in such projection areas as the dorsal hippocampus after 1 week of SB 269970 administration has also been reported by other researchers [42]. On the other hand, some authors have found that the 5-HT 7 receptor antagonist SB 269970 significantly inhibits 5-HT efflux [51]; however, other investigators have shown that inhibition of 5-HT release is likely to be mediated by 5-HT 7 receptor agonists [22].…”
Section: Discussionmentioning
confidence: 60%
“…To achieve a similar effect for standard antidepressants, at least 21-day treatment is necessary. Thus, the pharmacological blockade of 5-HT 7 receptors produces a considerably faster antidepressant-like response than do most antidepressant drugs [42]. Such a phenomenon may occur as a result of either an increased 5-HT 7 receptor activation or activation of other 5-HT receptors by an elevated extracellular 5-HT level due to the enhanced activity of serotonergic neurons.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations